A Novel In-Situ Nanoindentation Characterization of Phase Transforming Materials. Issue 1754 (27th February 2015) - Alipour Skandani, A.; Ctvrtlik, R.; Al-Haik, M.
ABSTRACT: Materials with different allotropes can undergo one or more phase transformations based on the changes in the thermodynamic states. Each phase is stable in a certain temperature/pressure range and can possess different physical and mechanical properties compared to the other phases. The majority of material characterizations have been carried out for materials under equilibrium conditions where the material is stabilized in a certain phase and a lesser portion is devoted for onset of transformation. Alternatively, in situ measurements can be utilized to characterize materials while undergoing phase transformation. However, most of the in situ methods are aimed at measuring the physical properties such as dielectric constant, thermal/electrical conductivity and optical properties. Changes in material dimensions associated with phase transformation, makes direct measurement of the mechanical properties very challenging if not impossible. In this study a novel non-isothermal nanoindentation technique is introduced to directly measure the mechanical properties such as stiffness and creep compliance of a material at the phase transformation point. Single crystal ferroelectric triglycine sulfate (TGS) was synthetized and tested with this method using a temperature controlled nanoindentation instrument. The results reveal that the material, at the transformation point, exhibits structural instabilities such as negative stiffness and negative creep compliance which is in agreement with the findings of published works on the composites with ferroelectric inclusions.